2018
DOI: 10.1103/physrevb.98.085124
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale plasmonic slot waveguides for enhanced Raman spectroscopy

Abstract: We theoretically investigate several types of plasmonic slot waveguides for enhancing the measured signal in Raman spectroscopy, which is a consequence of electric field and Purcell factor enhancements, as well as an increase in light-matter interaction volume and the Raman signal collection efficiency. An intuitive methodology is presented for calculating the accumulated Raman enhancement factor of an ensemble of molecules in waveguide sensing, which exploits an analytical photon Green function expansion in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…plasmonic) nanostructures and waveguides need be to be employed [ 55 ]. Wong et al [ 53 ] have reported a very thorough and complete analysis of various plasmonic waveguides. Additionally, they compared these with a conventional dielectric slot waveguide (DSW), used as a benchmark.…”
Section: Slot Waveguide Assisted Enhanced Raman Scatteringmentioning
confidence: 99%
See 2 more Smart Citations
“…plasmonic) nanostructures and waveguides need be to be employed [ 55 ]. Wong et al [ 53 ] have reported a very thorough and complete analysis of various plasmonic waveguides. Additionally, they compared these with a conventional dielectric slot waveguide (DSW), used as a benchmark.…”
Section: Slot Waveguide Assisted Enhanced Raman Scatteringmentioning
confidence: 99%
“…Figure 6 elucidates this concept, where an important design parameter can be extracted: the Purcell and the field enhancements contribute to the Raman scattering enhancement more than the larger light matter-interaction due to augmenting the interaction volume Ref. [ 53 ].
Fig.
…”
Section: Slot Waveguide Assisted Enhanced Raman Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Their integration leads to devices that are robust, cheap, mass-reproducible and reliable, and additionally allows parallelism [18]. In recent years, the silicon nitride (Si 3 N 4 ) platform was developed, which enables waveguide-based excitation and collection of Raman [19,20,21,22] and SERS spectra [23,24,25,26,27,28,29,30,31]. Despite the continuous improvement in the performance of the waveguide-based SERS platforms, they are limited by the background signal of the Si 3 N 4 [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…[37] Besides easier fabrication, the integrated nanotriangles also achieved a significant improvement in SERS enhancement compared to the integrated bowties. More recently, new waveguide-based SERS platforms have emerged, such as the nanoplasmonic slot waveguide [38,39,40,41] and the nanoporous gold on suspended silicon nitride waveguides [42].…”
Section: Introductionmentioning
confidence: 99%